2021
DOI: 10.3389/frobt.2021.726463
|View full text |Cite
|
Sign up to set email alerts
|

Rapidly Learning Generalizable and Robot-Agnostic Tool-Use Skills for a Wide Range of Tasks

Abstract: Many real-world applications require robots to use tools. However, robots lack the skills necessary to learn and perform many essential tool-use tasks. To this end, we present the TRansferrIng Skilled Tool Use Acquired Rapidly (TRI-STAR) framework for task-general robot tool use. TRI-STAR has three primary components: 1) the ability to learn and apply tool-use skills to a wide variety of tasks from a minimal number of training demonstrations, 2) the ability to generalize learned skills to other tools and manip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…They parametrized tool use with so-called p-tools, and demonstrated their technique with a wide range of tasks such as hammering and scooping in simulation or on a physical robot. Qin et al. (2021) developed an integrated system and learns basic tool use, rather than pre-define the tool usages as in other studies.…”
Section: Robot Tool Use Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…They parametrized tool use with so-called p-tools, and demonstrated their technique with a wide range of tasks such as hammering and scooping in simulation or on a physical robot. Qin et al. (2021) developed an integrated system and learns basic tool use, rather than pre-define the tool usages as in other studies.…”
Section: Robot Tool Use Literaturementioning
confidence: 99%
“…Manipulation skills focus on how to realize the required kinematics and dynamics of tool use actions. The actions include two components as defined in Qin et al (2021) and demonstrated in Figure 1: the contact poses and the course of the action. The contact poses include toolmanipulandum contact poses and gripper-tool contact poses (i.e., grasping).…”
Section: Introductionmentioning
confidence: 99%